Sosialisasi Dan Stop ! Perundungan Di Sekolah Menuju Lingkungan Sekolah Bebas Perundungan - Syafwar, Robi; Marwenny, Elwidarifa; Fauzi, Engrina; Wahyuni, Sry; Citra, Helfira; Harniwati, Harniwati; Falillah, Aulia; Puspita, Liza; Putra, Yolan Dwi (LPPM Universitas Dharma Andalas, 2024)
The Faculty of Law at Dharma Andalas University will conduct a community service activity in the form of a legal education campaign focusing on